2002
DOI: 10.1111/j.1651-2227.2002.tb02835.x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of linear growth and predictors of severe stunting during infancy in rural Malawi

Abstract: Stunting is common among children under 5 y of age in sub‐Saharan Africa. Several risk factors have been associated with poor growth but few studies have prospectively addressed the development of linear growth faltering and stunting during the first year of life. The present study was designed to analyse typical growth among rural Malawian infants, focusing particularly on the impact of birth size, adherence to feeding guidelines and morbidity in the development of severe stunting during infancy. A community‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

17
85
2
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(109 citation statements)
references
References 31 publications
17
85
2
5
Order By: Relevance
“…Others have shown that severe stunting is associated with preterm birth (,37 gestational weeks), maternal short stature (,160 cm), maternal failure to gain .200 g/week during pregnancy, inappropriate complementary feeding practices, frequent illnesses such as diarrhoea, home delivery and paternal illiteracy (3) , which may also have influenced the present results.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Others have shown that severe stunting is associated with preterm birth (,37 gestational weeks), maternal short stature (,160 cm), maternal failure to gain .200 g/week during pregnancy, inappropriate complementary feeding practices, frequent illnesses such as diarrhoea, home delivery and paternal illiteracy (3) , which may also have influenced the present results.…”
Section: Discussionmentioning
confidence: 71%
“…Stunting, which primarily affects children in their second year of life (2)(3)(4) , is a result of chronic inadequate intake of energy and nutrients, as well as frequent infections (1) .…”
mentioning
confidence: 99%
“…Prematurity is a common cause of infant mortality and its prevention has been suggested as crucial for the application of stunting management strategies (36,37) . Our results also demonstrated the influence of preterm delivery on stunting for the pooled sample.…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained are consistent with current evidence that suggests no strong correlation between breastfeeding and childhood overweight, 20 although some published studies have stressed the protective effect of breast milk against development of obesity. [21][22][23][24][25] Notably, breastfeeding has been extensively reported as having real influence on child growth and nutritional status up to the first year of life. [21][22][23][24][25] On the other hand, a study conducted among preschoolers aged 2 to 6 years in the city of São Paulo found a protective effect against overweight and obesity with 6 months of exclusive breastfeeding and 24 months or more of any breastfeeding.…”
Section: Discussionmentioning
confidence: 99%